Soil Nitrous Oxide Emission and Methane Exchange From Diversified Cropping Systems in Pannonian Region - Hüppi, Roman; Horváth, László; Dezső, József; Puhl-Rezsek, Marietta; Six, Johan (Frontiers in Environmental Science, 2022)
Diversified farming systems are promoted to improve ecosystem services in agriculture while maintaining productivity. Intercropping could improve soil quality, the stability of yields and climate resilience. Whether direct emissions of greenhouse gases from soil are reduced as well, depends on the specific measures of diversification. Here, we determined the greenhouse gas emissions from soils of two diversification experiments in the Pannonian climate of Hungary. Firstly, in an asparagus field, oat and field pea was introduced as intercrop between the asparagus berms. Secondly, grass and aromatic herbs were intercropped in a vineyard between the grape rows. The results show that especially for nitrous oxide, average treatment emissions can increase with additional legumes (+252% with intercropped field peas) but decrease with aromatic herbs (-66%). No significant changes were found for methane exchange. This shows that, while other ecosystem services can be increased by intercropping, changes in soil greenhouse gas emissions by intercropping are highly context dependent.